The Secretes of the Heavens as a Source of Provisions for all Creatures: Sciencing the Signs - Abdullahi, Auwal (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Life on the earth is dependent upon the provisions created by Allah the almighty. Many of these provisions are essentials for life on this world. This paper seeks to study the atmosphere, sky or heavens as a source for essential provisions needed for the sustenance of all living things (both plants and animals) by synthesizing scientific facts and the divine knowledge form Al-Qur’an and the Sunnah of Prophet Muhammad SAW. The paper found that all the essential needs of human beings and all other living creatures were made possible through the creation of heavens (Atmosphere) in addition to the protection it gives to life on earth. The paper therefore recommends that all people should be sensitized to protect the integrity of the atmosphere and to explore more ways to of using atmospheric resources to improve quality of life on earth.